Art and Spirituality: Exploring the Sacred and Transcendent in Human Existence - Dr. Sana Shah (Journal of Religion and Society, 2023)
This study investigates the intricate relationship between art and spirituality, delving into how artistic expression serves as a conduit for exploring the sacred and transcendent dimensions of human existence. Through an interdisciplinary approach drawing from psychology, anthropology, theology, and art history, it examines the historical, cultural, and psychological underpinnings of this connection. By analyzing diverse manifestations across cultures and epochs, this research sheds light on the transformative power of art in fostering spiritual growth and existential understanding. The findings underscore the significance of recognizing and cultivating the interplay between art and spirituality for individual well-being and societal cohesion in contemporary society.